Rancang Bangun Prototype Smart Dc House - Rosyid Idris, Ahmad; Rajab Husain, Muhammad; Noor, Nirwan A. (Jurusan Teknik Elektro Politeknik Negeri Ujung Pandang, 2022)
Solar energy is a source of livelihood for living things that is available in very large quantities, is not polluting, will not run out but is free. However, it is rarely found that the function and benefits of the sun are massive. One of the uses of solar energy is the use of solar cell panels as a renewable energy generator that can produce DC electricity. This study aims to design a smart DC home using a Solar Power Plant (PLTS). This study also aims to calculate the output power of the DC House. Accordingly, the research was conducted with hardware design and software design. Data collection is done by testing and observation techniques. Researchers based on research and discussion can say that they have succeeded in designing a Smart DC House with a total energy requirement used per day, which is 122.2 watt-hours per day. The output power obtained from the system is around 153 watt-hours per day with the specifications of the solar module used with a capacity of 50 Wp with a minimum battery capacity of 38 Ah. This system is built with a house size of 112 cm x 70 cm x 40 cm which consists of a bedroom, bathroom, living room, terrace, and kitchen with a microcontroller as a processor, the sensors used are LDR sensors, raindrop sensors, and infrared photodiode sensors. with the advantages of the system, namely the roof that can open and close automatically